Evaluation of durum wheat lines derived from interspecific crosses under drought and heat stress. Issue 1 (15th October 2020) - Aberkane, Hafid; Amri, Ahmed; Belkadi, Bouchra; Filali‐Maltouf, Abdelkarim; Kehel, Zakaria; Tahir, Izzat S. A.; Meheesi, Sara; Tsivelikas, Athanasios
Abstract: The productivity of durum wheat [ Triticum turgidum subsp. durum (Desf.) van Slageren] is affected by drought and/or high temperatures, challenges to be amplified by climate change. Pre‐breeding using wild relatives can supply useful traits for durum wheat improvement to adapt to major abiotic and biotic stresses. Sixty‐seven lines issued from backcrosses of Cham5 and Haurani durum wheat varieties with accessions of Triticum aegilopoides (Link) Bal. ex Koern., T. dicoccoides Koern. ex Schweinf., T. urartu Thumanian ex Gandilyan, and Aegilops speltoides Tausch were evaluated for drought and heat tolerance. The trials were conducted during two seasons (2016−2017 and 2017–2018) at Tessaout, Morocco, under full irrigation (optimal conditions) and rainfed conditions (drought stressed) and at Wed Medani, Sudan, under full irrigation combined with heat stress. The recurrent parents, along with eight best cultivars and elite breeding lines, were used as checks. Drought reduced the grain yield by 62%. Grain yield and drought tolerance index were used to identify lines to be used by breeding programs to enhance drought and heat tolerance. The derivatives lines 142014 (Cham5*3/ T. aegilopoides ), 142074 (Cham5*3/ T. dicoccoides ), and 142015 along with the checks Icarachaz and Gidara 2 ranked among the best under heat stress. Under drought stress, the lines 141972 (Haurani*2/ T. urartu ) and 141973 (Cham5*2/ T. dicoccoides ) yielded 196 and 142% of their recurrent parents' yield, respectively. High variation was found for agronomic and phenology traits, with heading time explaining 16% of grain yield under drought, while thousand kernel weight accounted for 18% of the yield under heat. We conclude that gene introgression from wild relatives pays off and can increase wheat resilience to cope with climate change effects. Core Ideas: Drought and heat stresses are the major abiotic stresses affecting wheat productivity. Wheat wild relatives are a reservoir of valuable traits for wheat breeding. Pre‐breeding should be supported to link conservation to use of crop wild relatives.